Formação inicial de professores: um estudo de caso sobre a participação de estudantes de pedagogia no Projeto Bolsa Alfabetização 2007 a 2009 - Moniz, Maria Isabel D'Andrade de Sousa (2010)
The initial teachers formation for Children Education and the First years of Fundamental School, which happens at the Licentiate course in Pedagogy, has been object of debates that takes place mainly in its curriculum and aspects as practice and stage. This dissertation inserts itself in these debates, considering curriculum in its extensive sense, which involves not only the courses curriculum programs, but equally, the several experiences lived by the students, in different spaces and times, direct or indirectly linked to the institutions. Among these experiences, this dissertation stands out the participation in the Bolsa Alfabetização project, implemented by the Secretaria da Educação do Estado de São Paulo, which objectives are to contribute with the first year children education and with the future teachers formation. Focusing on the teachers formation, the objective of this dissertation was to measure how the participation in the Bolsa Alfabetização project has contributed with the formation of a Pedagogy students group. The qualitative methodology was used, through a case study involving a group of students from an institution located in Grande São Paulo that participated in the project between 2007 and 2009. The data, collected by documental analysis, questionnaires, interviews and focal group, allowed to identify that there were significant contributions for the students formation, with their insertion in the first year public school classrooms. Besides the financial contribution represented by the received scholarship, it was possible to identify the apprenticeships about the classroom, the school, the literacy process and, finally, about teaching. Such apprenticeships were related to some context conditions in which they occurred, like the students longer stay in determined schools and classrooms, with a defined role and objectives and still the opportunities of group reflection that allowed the articulation between the apprenticeships at the graduation course and the ones experienced at the school space. In this way, this dissertation contributes with the continuation of the debates related to the initial teachers formation, proposing the planning of the formation opportunities so that the future teachers can experience the school on a daily basis in a more active, continuous and systematic way, promoting the articulation of the constructed knowledge in schools and classrooms of the licentiate course